Risk factors for Clostridioides difficile infection in children: a systematic review and meta-analysis. (December 2022) - Dong, N.; Li, Z.R.; Qin, P.; Qiang, C.X.; Yang, J.; Niu, Y.N.; Niu, X.R.; Liu, X.X.; Wang, W.G.; Wen, B.J.; Ouyang, Z.R.; Zhang, Y.L.; et al.
Summary: Background: Clostridioides difficile is considered an urgent threat to human health by the US Centers for Disease Control and Prevention. In recent years, C. difficile has been reported increasingly as a cause of gastrointestinal disease in children, and the prevalence of hospital-acquired C. difficile infection and community-acquired CDI in children is increasing. Aim: To perform a systematic review and meta-analysis of risk factors for CDI in children. Methods: MEDLINE/PubMed, EMBASE, Web of Science, Scopus, OVID, China National Knowledge Infrastructure, Wanfang (Chinese), SinoMed (Chinese) and Weipu (Chinese) were searched from inception to 12 th January 2022. Observational studies (cohort, case–control and cross-sectional) on CDI in children were included in the analysis. Data were pooled using a fixed or random-effects model, and odds ratios (OR) were calculated. Findings: In total, 25 observational studies were included in the analysis. Prior antibiotic exposure [OR 1.93, 95% confidence interval (CI) 1.25–2.97], prolonged hospitalization (OR 14.68, 95% CI 13.24–16.28), history of hospitalization (OR 3.67, 95% CI 1.91–7.06), gastric acid suppressants (OR 1.96, 95% CI 1.41–2.73), male gender (OR 1.18, 95% CI 1.05–1.32), neoplastic disease (OR 3.40, 95% CI, 2.85–4.07), immunodeficiency (OR 4.18, 95% CI 3.25–5.37), solid organ transplantation (OR 4.56, 95% CI 3.95–5.27) and enteral feeding (OR 2.21, 95% CI 1.05–4.62) were associated with increased risk of CDI. Conclusion: This systematic review and meta-analysis provides further evidence for the susceptibility factors of CDI to improve clinicians' awareness of CDI, and prevent C. difficile -associated diarrhoea in children.